Zoonotic Parasites of Reptiles: A Crawling Threat - Mendoza-Roldan, Jairo A. (Trends Parasitol, 2020)
Reptiles are reservoirs of a wide range of pathogens, including many protozoa, helminths, pentastomids, and arthropod parasitic species, some of which may be of public health concern. In this review we discuss the zoonotic risks associated with human–reptile interactions. Increased urbanization and introduction of exotic species of reptile may act as drivers for the transmission of zoonotic parasites through the environment. In addition, being a part of human diet, reptiles can be a source of life-threatening parasitoses, such as pentastomiasis or sparganosis. Finally, reptiles kept as pets may represent a risk to owners given the possibility of parasites transmitted by direct contact or fecal contamination. Awareness of reptile-borne zoonotic parasitoses is important to advocate control, prevention, and surveillance of these neglected diseases.